Working conditions in the acceding and candidate countries. - Paoli, Pascal; Parent-Thirion, Agnès (Luxembourg, 2003)
"Working conditions in the acceding and candidate countries provides the first important benchmark of the situation in all 13 countries. Gauging the status on issues ranging from stress in the workplace to types of employment or working hours, the report attempts to portray a realistic picture of the working environment of these countries as the take this critical step towards an enlarged Europe. "